Retroviral vectors for gene therapy - Maier, Patrick; Kalle, Christof von; Maier-Laufs, Stephanie (Future microbiology, 2010)
Since their first clinical trial 20 years ago, retroviral (gretroviral and lentiviral) vectors have now been used in more than 350 gene-therapy studies. Retroviral vectors are particularly suited for gene-correction of cells due to long-term and stable expression of the transferred transgene(s), and also because little effort is required for their cloning and production. Several monogenic inherited diseases, mostly immunodeficiencies, can now be successfully treated. The occurrence of insertional mutagenesis in some studies allowed extensive analysis of integration profiles of retroviral vectors, as well as the design of lentiviral vectors with increased safety properties. These new-generation vectors will enable us to continue the successful story of gene therapy, and treat more patients and even more complex diseases.